Factors Affecting the Use of Accrual Based Financial Statements for Regional Device Organizations (OPD) of South Sumatera Province - Maimunah, Mutiara; Kadir, Syamsurijal A.; Bastian, Indra; Wahyudi, Tertiarto (International Journal of Economics and Financial Issues, 2018)
The purpose of this study was to examine and find out the influence of accrual accounting knowledge, administrative bureaucracy, and Regional Management Information System (SIMDA) on the Use of Accrual Accounting. The research method used is an explanatory research. The scope of this study is the public sector, especially in the accounting unit at the Regional Device Organization (OPD) in the Government of South Sumatera Province. The data used are primary data in the form of the results of the respondents’ answers taken with a questionnaire instrument. The results of data analysis in this study is that Accrual Accounting Knowledge, Regional Management Information System (SIMDA) and Administrative Bureaucracy together influence the Accrual Accounting Knowledge. The interpretation that can be explained from these results is the Use of Accrual Accounting will be effective if there is a high level of Accrual Accounting Knowledge, a reliable Regional Management Information System (SIMDA) and a short or practical Administrative Bureaucracy. Keywords: SIMDA, Financial Statements, Accrual Base, Regional Device Organizations JEL Classifications: H80, H83, M41 DOI: https://doi.org/10.32479/ijefi.7226